Surface Structure Characterization of Shape and Size Controlled Pd Nanoparticles by Cu UPD: A Quantitative Approach - Garnier, Emmanuel; Vidal-Iglesias, Francisco J.; Feliu, Juan M.; Solla-Gullón, José (Frontiers in Chemistry, 2019)
The search of new surface sensitive probes to characterize the surface structure of shape and size-controlled nanoparticles is an interesting topic to properly understand the correlations between electrocatalytic properties and surface structure at the nanoscale. Herein, we report the use of Cu UPD to characterize not only qualitatively but also quantitatively the surface structure of different Pd nanoparticles with controlled particle shape and size. Thus, Pd nanoparticles with cubic, octahedral and rhombic dodecahedral shape, that is, with preferential {100}, {111} and {110} surface structures, respectively, were prepared. In addition, cubic Pd nanoparticles with different particles sizes and spherical (2-3 nm) Pd nanoparticles were also synthesized. Based on the Cu UPD results on Pd single crystals, a new approach is proposed to qualitatively and quantitatively determine the percentages of {100}, {111} and {110} surface domains present at the surface of the different shape and size controlled Pd nanoparticles. The results reported clearly show the benefits of this Cu UPD to get detailed information of the surface structure of the nanoparticles according with their particle shape and size.